Determination of the parameters of plasticity models of geological media on the base of computer simulation; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Astafurov S. V.; Shilko E. V.; Dimaki A. V.; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen